RNAi-Mediated Resistance Against Viruses in Perennial Fruit Plants - Singh, Khushwant; Dardick, Chris; Kumar Kundu, Jiban (Plants (Basel, Switzerland), 2019)
Small RNAs (sRNAs) are 20-30-nucleotide-long, regulatory, noncoding RNAs that induce silencing of target genes at the transcriptional and posttranscriptional levels. They are key components for cellular functions during plant development, hormone signaling, and stress responses. Generated from the cleavage of double-stranded RNAs (dsRNAs) or RNAs with hairpin structures by Dicer-like proteins (DCLs), they are loaded onto Argonaute (AGO) protein complexes to induce gene silencing of their complementary targets by promoting messenger RNA (mRNA) cleavage or degradation, translation inhibition, DNA methylation, and/or histone modifications. This mechanism of regulating RNA activity, collectively referred to as RNA interference (RNAi), which is an evolutionarily conserved process in eukaryotes. Plant RNAi pathways play a fundamental role in plant immunity against viruses and have been exploited via genetic engineering to control disease. Plant viruses of RNA origin that contain double-stranded RNA are targeted by the RNA-silencing machinery to produce virus-derived small RNAs (vsRNAs). Some vsRNAs serve as an effector to repress host immunity by capturing host RNAi pathways. High-throughput sequencing (HTS) strategies have been used to identify endogenous sRNA profiles, the "sRNAome", and analyze expression in various perennial plants. Therefore, the review examines the current knowledge of sRNAs in perennial plants and fruits, describes the development and implementation of RNA interference (RNAi) in providing resistance against economically important viruses, and explores sRNA targets that are important in regulating a variety of biological processes.
Keywords: viruses; resistance; next generation sequencing; perennial plants; sRNA